Effective polyurethane compositions filled with industrial wastes - Margarita Alexandrovna, Goncharova; Anastasia Olegovna, Korneeva; Oleg Olegovich, Korneev; Ghalib Hussain Al-Surraiwy, Hameed (International Journal of Engineering and Technology, 2018)
Formulations are developed and optimized for of rigid polyurethane foams filled with converter slag. The optimum content of the filler is 30%. Polyurethane compositions have the following characteristics: average density â€“ 42.59 kg/m3, compressive strength at 10% deformation â€“ 0.293 MPa, water absorption by volume 1.71%, coefficient of thermal conductivity â€“ 0.028 W/mÂ·0C. Polyurethane foams are applied in sandwich panels, multi-layer roof constructions and for the manufacture of fixing systems for metal rolled.Sandwich panels with polyurethane foam insulation and sheathing of specialized panels are designed for the construction of pre-fabricated residential buildings. The forecasting of polyurethane durability in building structures as thermal insulation in sandwich panels the foam lifespan is about 75 years, which is approximately two times greater than that of the unreinforced foam.Layered roof structures with modified rigid polyurethane foam are used for buildings and structures for various purposes. Their use makes it possible to solve several tasks: creating a complete architectural image, ensuring high strength and deformation characteristics with good noise and heat insulation, minimization when mounting. The use of lightweight, transportable and technologically advanced roofing elements in conditions of mass production creates significant opportunities for industrial construction. The proposed foam fixing systems during shipping rolled metal in containers makes it possible to exclude the possibility of the longitudinal and transverse shift of pallets with rolls, to protect metal from damage, to simplify the design of the foxing elements, reduce the production cost, and minimize the amount of time for fixing metal rolls in the container.Â Â